Demographic and attitudinal determinants of organic food consumers - Damo, Maria Olga O. (Animo Repository, 2003)
This study uses both exploratory and descriptive methods of research to determine the demographic variables and attitudes that affect consumer awareness and consumption of organic foods. The first phase of the study uses Focus Group Discussion. In the second phase, descriptive research is used in the form of a survey using questionnaire based on results of the Focus Group Discussions. The study is conducted within two cities in Metro Manila, namely Makati and Mandaluyong. The subjects investigated, taken through purposive quota sampling, are people who either have visited the Rustan's Supermarket in Glorietta or in Back to Basics store in Robinson's Galleria at least once or those who are frequent shoppers of said places within the month of May, 2002. Data gathered on the focus groups discussions and survey were treated using gamma statistics. Results of the study showed that forty percent (40%) of the statements pertaining to the Classical Marketing Concept were supported, demonstrating inverse relationship between the agreement to the concept of consuming food products that are ready to cook and that give them the feeling of a full stomach, and organic food consumption. Eighty percent (80%) of the statement pertaining to the Product Concept were strongly supported, demonstrating inverse relationship between the agreement to the concept of consuming food products that were treated to maintain its taste longer and its fresh look to make it more appealing and those that satisfy them more than those produced by other companies, and organic food consumption. On the other hand, results showed that thirty-three percent (33%) of the statements pertaining to the Production Concept were controverted. The more the consumers eat foods that are cheap and affordable, and are widely available, the more likely they will consume organic foods. Sixty-two percent (62%) of the statements pertaining to the Sustainable Marketing Concept were also supported, demonstrating direct relationship between the agreement to the concept of consuming food products that are good for the body; that are nutritional and healthy; and are good for the environment and society; and that organic foods will help prolong life, and organic food consumption. The survey showed a one hundred percent (100%) support to the statements that organic foods are good for those people undergoing medical treatment to prevent sickness from becoming worse, and those concerned with physical fitness. Partial support (50 %) was given to the statement of consuming products that are easy to prepare, demonstrating an inverse relationship with organic food consumption. Statements that pertain to the consumers' willingness to other other products out of curiosity and organic food consumption were not significantly related. The statements that pertain to the consumers' willingness to try other products out or boredom and organic food consumption were 100% not supported.